Transcriptomic profiling of clear cell renal cell carcinoma reveals age-dependent molecular signatures and clinical stratification patterns - Yun Niu; Yunchao Su; Xiaoxi Wang; Xiaoyuan Yang; Dingrong Zhong (PLoS ONE, 2026)
Clear cell renal cell carcinoma (ccRCC) represents the most prevalent form of kidney cancer, yet age-related molecular heterogeneity remains poorly characterized in clinical specimens. We performed comprehensive transcriptomic profiling of 73 formalin-fixed paraffin-embedded (FFPE) ccRCC samples using RNA sequencing to investigate age-dependent molecular signatures and their clinical implications. Principal component analysis (PCA) revealed that PC1 significantly separated younger versus older patients (p = 0.04), while PC2 distinguished tumors by gender (p = 0.00012), size (p = 8 × 10 ⁻ ⁴), and histological class (p = 0.043), suggesting an orthogonal aging molecular axis alongside with disease progression. Differential gene expression analysis identified 330 age-associated genes, with elderly patients showing upregulation of immune checkpoint regulators (CD70), apoptosis modulators (DEDD, HTATIP2), and proton pump components (TCIRG1), alongside downregulation of metabolic enzymes (DIO2) and cytoskeletal regulators (MICALL2). Pathway enrichment analysis revealed dysregulation of aldosterone-regulated sodium reabsorption, B cell receptor signaling, and Th17 cell differentiation pathways, reflecting age-related immunometabolic reprogramming. Integrative analysis of DEGs across clinical variables identified 1,536 shared genes between tumor size and stage comparisons, with CK7-positive tumors exhibiting distinct transcriptional profiles potentially representing a novel molecular subtype. These findings demonstrate that aging fundamentally alters the ccRCC transcriptome through coordinated changes in immune surveillance, metabolic homeostasis, and tumor microenvironment composition, providing a molecular framework for age-stratified therapeutic approaches and precision oncology strategies in renal cell carcinoma.